Clinical predictors of radiological pneumonia in children with severe community acquired pneumonia - Hafiz, Aamir; Wani, Nisar Ahmed; Bhat, Abdus Sami; Jan, Muzafar (International Journal of Contemporary Pediatrics, 2023)
Background: Pneumonia causes one-third of all under 5 deaths from infections. Typically cough, fever, pleuritic chest pain, fatigue and loss of appetite are presenting symptoms of pneumonia. Even though chest radiograph improves the diagnosis of paediatric community acquired pneumonia to a certain degree, however its interpretation is subjective, moreover exposure to ionizing radiation, cost, the time and space used, and the need to wait for the radiograph and to see the clinician again limits its use in in resource limited settings. In this study, it was aimed to determine clinical predictors of radiological pneumonia in children with severe community acquired pneumonia which may help in judicious use of X-ray and rational management with antibiotics, in these children. Methods: This was a case control, observational study which was conducted in post graduate department of paediatrics, children hospital on all paediatric patients between ages 2 months and 5 years, who presented to the paediatric emergency department and were diagnosed with severe community acquired pneumonia as per World Health Organization (WHO) guidelines, were included. Results: The study was conducted on 100 cases of severe radiological pneumonia and 200 controls of non-radiological pneumonia. From admission to discharge, children were followed and multiple clinical parameters were compared. Among 100 cases, 72 (72%) had wheezing, 70 (70%) had cyanosis, 67 (67%) had tachypnea, 67 (67%) had hypoxemia, 59 (59%) had grunting, and 42 (42%) had bronchial breathing. Similarly, among 200 controls, 165 (82.5%) had wheezing, 116 (58%) had cyanosis, 97 (48.5%) had tachypnea, 58 (29%) had hypoxemia, 90 (45%) had grunting and 19 (9.5%) had bronchial breathing. The difference is statistically significant. Conclusions: It can be concluded from our study that presence of cyanosis, tachypnea, hypoxemia, grunting and bronchial breathing are the positive predictors of radiological pneumonia, while as presence of wheezing are negative predictors of radiological pneumonia.